2018
DOI: 10.1002/2017jb014871
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Method for Static Stress Drop and Application to the 2011 Mw9.0 Tohoku‐Oki Earthquake

Abstract: Seismic stress drop is a fundamental parameter for the investigation of earthquake mechanism. In general, it is indirectly predicted by fault slip based on the dislocation source model or seismic moment; inversion for the stress change on faults has not received the deserved attention. In this study, we propose a finite element method to invert the stress drop on fault, constrained by the observed coseismic deformation. Rupture termination and displacement on fault are automatically predicted from the model. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 30 publications
(47 reference statements)
3
17
0
Order By: Relevance
“…Furthermore, the agreement between the two smaller seismogenic asperities predicted in this study also compare well with the areas of the two largest aftershocks. In addition, the predicted depth of the seismogenic asperity of the mainshock by the contour of zero-shear stress is consistent with that of the rupture termination identified 13 , marked by black-dish line in Fig. 2a.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Furthermore, the agreement between the two smaller seismogenic asperities predicted in this study also compare well with the areas of the two largest aftershocks. In addition, the predicted depth of the seismogenic asperity of the mainshock by the contour of zero-shear stress is consistent with that of the rupture termination identified 13 , marked by black-dish line in Fig. 2a.…”
Section: Discussionsupporting
confidence: 78%
“…But the centers of both predicted areas were much deeper (35–40 km) than that of our seismogenic asperity (~15 km). The agreement of the latter with the rupture area of the mainshock 13 is strong evidence for the reliability of the present method. Furthermore, the agreement between the two smaller seismogenic asperities predicted in this study also compare well with the areas of the two largest aftershocks.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In real earthquake sequences, stress drops most likely exhibit spatial variations, creating a stress drop distribution. Recent studies have reported spatial and temporal variations in stress drop in California (Shearer et al, 2006;Allmann and Shearer, 2007;Abercrombie, 2014), Japan (Oth et al, 2011;Yoshida et al, 2017;Xie and Cai, 2018), and New Zealand (Oth and Kaiser, 2014). In these papers the stress drops associated with major earthquakes cannot be treated as a mere progression from low to high values between major events; rather, they demonstrate subtler changes in the character of a stress field on a fault (Hardebeck and Aron, 2009;Candela et al, 2009).…”
Section: Introductionmentioning
confidence: 99%